2008
DOI: 10.1021/bm7012668
|View full text |Cite
|
Sign up to set email alerts
|

New Approach to Elaborate Exfoliated Starch-Based Nanobiocomposites

Abstract: The present paper reports the successful elaboration of exfoliated plasticized starch-based nanobiocomposites. This was made possible by using cationic starch as a new clay organomodifier to better match the polarity of the matrix and thus to facilitate the clay exfoliation process. To demonstrate the efficiency of this new approach, either natural (MMT-Na) or organomodified (OMMT-CS) montmorillonite were incorporated into the starch nanobiocomposites by a melt blending process. The morphological analyses (SAX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
101
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 136 publications
(115 citation statements)
references
References 23 publications
12
101
1
1
Order By: Relevance
“…But only a small increase in the d 001 was achieved. Nevertheless, this approach was successfully applied in a previous publication, 94 with cationic starch (CS) as MMT organo-modifi er. According to these authors, no diff raction peak was observed by X-Ray diff raction, suggesting an exfoliated morphology, which was confi rmed by TEM analysis (Fig.…”
Section: Structures Of Mmt-based Nano-biocompositesmentioning
confidence: 99%
“…But only a small increase in the d 001 was achieved. Nevertheless, this approach was successfully applied in a previous publication, 94 with cationic starch (CS) as MMT organo-modifi er. According to these authors, no diff raction peak was observed by X-Ray diff raction, suggesting an exfoliated morphology, which was confi rmed by TEM analysis (Fig.…”
Section: Structures Of Mmt-based Nano-biocompositesmentioning
confidence: 99%
“…41 The surfactant in the interlayer space can be regarded as an aggregate, since phase transition of the dioctadecyldimethylammonium ion intercalated in smectites has been reported and the phase transition between the gel and liquid-crystalline phases affected the diffusion and reaction of solute molecules. 43,44 However, new tendencies in organoclays preparation focus on the use of non-toxic modifiers of biological origin such as lecithin based tensioactives 45 or diverse biopolymers 46 instead of the conventional surfactant quaternary ammonium based agents because their ''bio-friendly'' character may enlarge their applications to the food, pharmaceutical and biomedical fields. 41 Some examples of these materials are discussed in sections below.…”
Section: Introductionmentioning
confidence: 99%
“…Small molecules such as glycerol and water that can form hydrogen bonds with starch can serve as plasticizers in starch-based materials. A part of the plasticizers can potentially be absorbed on the clay surface, influencing the interfacial strength and stress transfer between the polymeric matrix and clay (Chivrac, Pollet, Schmutz, & Averous, 2008). Depending on the relative humidity, the moisture content (plasticizer concentration) of the starch-clay nanocomposites will change and consequently influence the Young's modulus of the materials (Avella et al, 2005;Huang, Yu, & Ma, 2006;Ma, Yu, & Wang, 2007;Perez, Alvarez, Mondragon, & Vazquez, 2008).…”
Section: Introductionmentioning
confidence: 99%